Performance analysis of 5G NR network planning at 2300 MHz in Indonesia: A comparative study of LoS and NLoS scenarios - Putri Rahmawati; Lia Hafiza; Muhammad Adam Nugraha; Syifa Maliah Rachmawati (Institute of Advanced Engineering and Science, 2026)
This study presents a systematic comparative analysis of 5G new radio (NR) network planning at 2300 MHz for Bandung City, Indonesia, evaluating line-of-sight (LoS) and non-line-of-sight (NLoS) propagation scenarios to determine infrastructure requirements and performance characteristics for urban deployment. Employing the 3GPP TR 38.901 Urban Macro propagation model, link-budget analysis, and Atoll-based simulation for a 167.31 km² urban area, the study evaluates coverage performance under projected 2025 deployment conditions. The results reveal significant differences between propagation scenarios. LoS conditions require 45 gNodeBs for uplink coverage, achieving a synchronization signal reference signal received power (SS-RSRP) of -94.63 dBm and a synchronization signal signal-to-interference-plus-noise ratio (SS-SINR) of 10.87 dB, both categorized as “Good.” In contrast, the NLoS scenario requires substantially denser deployment with 635 gNodeBs, resulting in improved SS-RSRP performance of -71.98 dBm (“Excellent”) and SS-SINR of 12.32 dB (“Good”), along with more uniform coverage distribution. The findings indicate that improved KPI performance and coverage uniformity in NLoS environments can be achieved through substantially increased infrastructure density, highlighting the trade-off between network quality, deployment complexity, and infrastructure cost in urban 5G NR planning.